Pengaruh Plus-minus bayang-bayang matahari terhadap penerusnya waktu shalat dzuhur dan ashar - Inda Junita; , Mahyuddin Latuconsina; . Intan Cahyani (HISABUNA: Jurnal Ilmu Falak, 2023)
This study discusses the shadow of the sun with the main problem, namely whether the plus-minus of the shadow of the sun affects the determination of the time of dzuhur and ashar prayers? The author uses a qualitative type of descriptive research with syar'i shorts based on the Qur'an and hadith as well as an astronomical approach by making direct observations using the istiwa' stick to find out the shadow of objects during dzuhur and ashar prayers. This method of determining the time of prayer using the shadow of the sun and the istiwa stick tool is considered that the resulting level of accuracy is very high. And it can be used as an alternative in determining the time of dzuhur and ashar prayers with the shadow of the sun. As for this study, we must pay attention to the plus-minus where what is meant is when the weather is cloudy and sunny which can be used as a standardization in determining the time of dzuhur and ashar prayers. Researchers hope that in the future, they will increase knowledge related to the influence of plus-minus solar shadows on determining the time of prayers dzuhur and ashar yan can be used as a reference in determining the time of prayer, the most important thing is that the object has a shadow in this case the sun.